SIMULATION OF THE IMPACT OF SEA LEVEL RISE ON MORPHOLOGICAL CHANGE IN THE COASTAL REGION OF MEKONG RIVER - Vinh, Vu Duy; Lan, Tran Dinh; Tu, Tran Anh; Anh, Nguyen Thi Kim (Vietnam Journal of Marine Science and Technology, 2015)
This paper presents some study results on morphological change in the coastal region of Mekong River under the influences of sea level rise. In order to set up the models, measured data were collected, systematically and homogeneously processed to create open boundary conditions (time-serial data) for the model. Open sea boundary conditions of the model were created by NESTING method. The model (Delft3D model) was set up with 4 layers in Sigma coordinate. The results of model were validated, showing a fairly good agreement with measured data (water elevation, currents, and suspended sediment concentration) at some places in the study area. Results of some scenarios of simulation (dry and flood season) show the sea level rise due to climate change could make a reduction in the seaward sediment transport and increase its settling around estuaries. As a result, sea level rise causes an increase in the accreted rate of sandbars in southern estuary of Mekong river coastal area. The influences of sea level rise on Mekong river coastal bed topography are prevailing in the region of about 7 - 10 km seawards. Further 10 km from the coast, influences of sea level rise on coastal morphology are not significant.